In situ synthesis of ZnO–GO/CGH composites for visible light photocatalytic degradation of methylene blue. Issue 70 (12th December 2019) - Di, Xiaoxuan; Guo, Feng; Zhu, Zihan; Xu, Zhonghao; Qian, Ziqi; Zhang, Qian
Abstract : A novel ZnO–GO/CGH composite was prepared using an in situ synthesis process for photodegradation of methylene blue under visible light illumination. Abstract : A novel ZnO–GO/CGH composite was prepared using an in situ synthesis process for photodegradation of methylene blue under visible light illumination. The chitin–graphene composite hydrogel (CGH) was used to provide uniform binding of the nano ZnO–GO composite to the hydrogel surface and prevent their agglomeration. GO provides multi-dimensional protons and electron transport channels for ZnO with a flower-like structure, which possessed improved photo-catalytic activity. SEM analysis indicates that the hydrogel has good adsorption properties with rougher surfaces and porous microstructure, which enables it to adsorb the dyes effectively. Under synergetic enhancement of adsorption and photo-catalysis, catalytic activity and nano ZnO–GO/CGH recycling improved greatly. Synthesized nano ZnO–GO/CGH showed high dye removal efficiency of 99%, about 2.2 times that of the pure chitin gel under the same condition. This suggests the potential application of the new photocatalytic composites to remove organic dyes from wastewater.